Return to professional football (soccer) matches after ACL ruptures - Roi, G. S.; Nanni, G.; Tavana, R.; Tencone, F. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The injuries of the Anterior Cruciate Ligament (ACL) are very invalidating events that require a surgical treatment and that keep many players out of competition for many months every season. It is well known that after ACL reconstruction an accelerated rehabilitation (Shelbourne & Nitz, 1990) allows the players to return to official matches within about 3-4 months, but there are no epidemiological data on professional football. The aim of this retrospective study was to investigate the time to return to official competitions after ACL reconstruction. Methods Data were collected by the team physicians of the professional teams competing in the Italian First League Championship, filling in a form during the October-December 2002 period. The study involved 479 players. We found 41 players (11%) who underwent one or more than one ACL reconstruction during their career. Five players were excluded because it was impossible to have exactly the time to return to competitions and the diagnosis. So the total number of ACL ruptures considered in this study was 38. Results The mean time to return to competitions was 232±135 days from surgery (range 76-791). 12 players reported an isolate ACL rupture and returned to competitions within 163±44 days (range: 76-231). 20 players reported one or more associated lesions (medial or lateral meniscus and medial collateral ligament) and returned to competitions within 203±56 days (range: 146-329). 6 players reported complications during the operative or rehabilitation periods (swelling, infections) and returned to competition within 456±203 days (range: 233-791). Discussion/Conclusion The data of the present study indicate that a fast (<4 months) return to competition was possible only in three cases of isolated ACL rupture. In the cases of isolated rupture, the mean time to recovery and to return to competitions was about five months, although a faster return, up to 76 days, was possible. In the cases of ACL ruptures with associated lesions or complications, the mean time to recovery is more than six months, with a wide range of time, up to more than 12 months. The data of the present study must be considered by the coaches and the managers of the professional teams because the time to return to official competitions may have important sports as well as economical consequences nd the pressure to return to pre injury competitive levels is immense, especially for the professional football players.